Re: Reminder of submitting the coordinated drawing on M&E design - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the reminder to submit the coordinated drawing on M&E design for BRACU new campus project.